Giant Ovarian Cyst Masquerading as Massive Ascites in an 11-Year-Old - Shaza Ali Mohammed Elhassan; Shabina Khan; Ahmed El-Makki (Case Reports in Pediatrics)
We are presenting a unique case of an 11-year-old girl admitted for investigation of progressive abdominal distention of more than one-year duration. Due to the complete cystic nature of the mass and its enormous size, it was not visualized by the ultrasound and was reported as massive ascites. MRI and postoperative histopathology confirmed a diagnosis of giant serous cystadenoma of the right ovary. She underwent a right ovarian cystectomy with complete preservation of both ovaries and fallopian tubes and is doing well on outpatient follow-up.